Hi, I'm totally stuck!

Problem: sqrt(x-3) = sqrt (2) -sqrt(x)

I know I square them to get them out of square roots but after that I'm stuck-
answers: -25/8
25/8
no solution
1/8
Please show me how its done
Thank you

3 answers

x - 3 = 2 - x
add x to both sides
2x - 3 = 2
Add 3 to both sides
2x = 5
divide by 2
x = 2.5
square both sides

x-3 = 2 - 2√(2x) + x
2√(2x) = 5
√2x = 5/2
square again
2x = 25/4
x = 25/8

BUT, since we squared our equation, we have to verfify each answer

LS = √(3-25/8) = appr. .3536
RS = √2 - √(25/8) = appr. -.3536

so LS ≠ RS, and thus there is NO SOLUTION.
Thank you
Similar Questions
  1. Evaluate sqrt7x (sqrt x-7 sqrt7) Show your work.sqrt(7)*sqrt(x)-sqrt(7)*7*sqrt(7) sqrt(7*x)-7*sqrt(7*7) sqrt(7x)-7*sqrt(7^2)
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 2 answers
  2. what is the simplified form of 3 sqrt (5c) x sqrt (15c^3)choices are a. 15c^2 sqrt (3) b.6c^2 sqrt (5) c. 5c^2 sqrt(3) d. 12c^4
    1. answers icon 1 answer
more similar questions